The Possibililies of Artificial Intelligences (AI) In English Learning: Lecturers and Students Perceptions - Anugrah, Achsan (La Parole : Journal of Language Teaching and Pedagogy, 2018)
This research was conducted to see the possibility of using artificial intelligence in the process of learning English in the English Language Study Program at the Universitas Muhammadiyah Parepare. Especially their understanding and perspective of lecturers and students on the use of artificial intelligence in the process of learning English. This study uses Descriptive Qualitative by design taking two groups of subjects namely, subject from students and lecturers. The population of this study is the Department of English Language Education, Universitas Muhammadiyah Parepare. The subject of this study consisting of 14 subjects. the 14 subjects taken from the total subject in which 10 subjects from students and 4 subjects from lecturers. The results of the study indicate that the tendency of students still lacks understanding of what Artificial Intelligence is and for the use and effects of its use students understand that it is very useful and helps them and lecturers. From their perceptions related to the use of artificial intelligence in English language learning, students do not agree on full use in the learning process. As for the lecturers' subject, all said it was very possible, but in order to fully spread it, it still could not.